MAGNETISM EFFECT ONTO ALUMINA TOWARDS THE MALACHITE GREEN REMOVAL IN AQUEOUS SOLUTION - Northaqifah Hasna Mohamed Khir; Nur Fatien Muhamad Salleh; Aina Sofiya Mahat; Nurqasrina Iffah Ruslan; Mohd Shahrul Nizam Salleh; Adibah Mohd Noor (Marine Frontier, 2024)
Removal of hazardous effluents from the wastewater is crucial for sustainable effluent management. Since industrial activities keep rising to meet the global demand, it is a major concern to monitor the waste management to protect our environment. Dyes and heavy metals are major effluents coming from the industries. Despite other technologies, the ability of magnetic alumina to adsorb one of the carcinogenic dyes, malachite green in an aqueous solution was investigated as an alternative adsorbent due to its low cost, ease of find and higher binding capacities. The synthesized adsorbents were categorized into three different magnetism compounds giving three composites of CoAl, FeAl and NiAl. Chemical characterization using KBr FTIR indicates the presence of hydroxyl groups, alumina and metal stretching in the structure of the magnetic alumina for all composites The adsorption of malachite green was conducted with a variation contact time of 15–180 min. Malachite green was best removed by FeAl at 90 minutes with 97% percent removal.